Essential fashion illustration : digital - Streeter, Loreto Binvignat (Rockport Publishing, 2010)
Essential Digital Fashion Illustration' is a complete, in-depth tutorial that guides readers step-by-step through the digital techniques typically employed in fashion design and illustration.- Resumé vydavatel